6(x+2)+2x=46

Simple and best practice solution for 6(x+2)+2x=46 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x+2)+2x=46 equation:


Simplifying
6(x + 2) + 2x = 46

Reorder the terms:
6(2 + x) + 2x = 46
(2 * 6 + x * 6) + 2x = 46
(12 + 6x) + 2x = 46

Combine like terms: 6x + 2x = 8x
12 + 8x = 46

Solving
12 + 8x = 46

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12' to each side of the equation.
12 + -12 + 8x = 46 + -12

Combine like terms: 12 + -12 = 0
0 + 8x = 46 + -12
8x = 46 + -12

Combine like terms: 46 + -12 = 34
8x = 34

Divide each side by '8'.
x = 4.25

Simplifying
x = 4.25

See similar equations:

| a/-3-6=5 | | 9.27777777778= | | x*7+13=55 | | y=-1/3X+7 | | 4(m-3)=2(m-4.5) | | (4x+6)=6x+9 | | (x+8/12)=1(-3/4x) | | 6+18x-5=8x+76-5x | | 1x+2y=5 | | 5x+4+2x=53 | | 2k(k+13)=13 | | 6x+3-4x=21 | | (x+8/12)=1-3/4x | | 9x1+5/18 | | V^6+2v^2+7/v^2 | | 3x+2x+6=41 | | 9x15/18 | | 8p+7p=60 | | 2*0/3=4+y | | 4x+3+3x=7x+3 | | X+X+27+3X-33=764 | | -11.6x=104.4 | | 3x^2+5x-1=7x+7 | | -3/7(m-9)=3+6m | | 13x-2(3x+4)=22 | | 2*0/1=4+y | | x/5=14/35 | | 13x-2(3x+4)=32 | | -(6y+1)-(-5Y-4)=-5 | | 6x-54=3x-12 | | x+0.2x=36 | | 13x-143=6x-10 |

Equations solver categories